2019
DOI: 10.1177/2058738419847852
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variants on chromosome 9p21 confer risks of cerebral infarction in the Chinese population: a meta-analysis

Abstract: Ischemic stroke (IS) is the leading cause of disability. Researchers have demonstrated that IS is more a multifactorial disorder than a single-factor disease. At present, no consistent conclusions have been reached on susceptibility loci for IS on chromosome 9p21. We conducted this meta-analysis to verify whether genetic loci on chromosome 9p21 reported domestically and abroad could be responsible for IS in Chinese populations. We analyzed data from eight studies that covered a total of 9756 individuals with C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Notably, studies investigating the genetic associations of chromosome 9p21 variants have mainly been performed among Caucasian populations, and relatively few studies have been carried out in Han Chinese populations. Although Chen et al (2019) studied chromosome 9p21 variants in Chinese populations, they concluded that mutations in rs2383207 may reduce the risk of IS but reported no definite correlation between rs10757278 and IS ( Chen et al, 2019 ). In the present study, we once again focused on the relationship between stroke and chromosome 9p21.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, studies investigating the genetic associations of chromosome 9p21 variants have mainly been performed among Caucasian populations, and relatively few studies have been carried out in Han Chinese populations. Although Chen et al (2019) studied chromosome 9p21 variants in Chinese populations, they concluded that mutations in rs2383207 may reduce the risk of IS but reported no definite correlation between rs10757278 and IS ( Chen et al, 2019 ). In the present study, we once again focused on the relationship between stroke and chromosome 9p21.…”
Section: Discussionmentioning
confidence: 99%
“…Cacabelos et al (2018) and Yee et al (2019) showed that the C7673T polymorphism of APOB gene was significantly associated with the risk of ischemic stroke. Chen et al (2019), Nordestgaard et al (2018) confirmed that the polymorphism of ϵ 2,ϵ3,ϵ4 of APOE gene was associated with ischemic stroke. APOB gene and APOE gene are both known ischemic stroke susceptibility genes because of blood lipid level.…”
Section: Introductionmentioning
confidence: 61%
“…This study has evaluated the association of genetic polymorphism rs2383207 (9p21.3) with occurrence of atherosclerosis in Caucasian and Asian populations. Previous studies reported about the association of rs2383207 (A) risk allele with cardiovascular diseases (CAD) [ 14 ], presentation of CAD [ 15 ] and severity of CAD [ 12 ]. Akinyemi et al reported that rs2383207 increases ischemic stroke (IS) incidence in indigenous West African men [ 16 ].…”
Section: Discussionmentioning
confidence: 99%